EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING TERHADAP KEMAMPUAN REGULASI EMOSI PADA SISWA DI SANGGAR BELAJAR PANDAN - Sri Ngayomi Yudha Wastuti; Nazwa, Nazwa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Emotional regulation is important for student learning success and social adjustment. At Sanggar Belajar Pandan, Malaysia, students still face challenges in managing their emotions while learning. This study aims to determine the effectiveness of group counseling using role-playing techniques in improving student emotional regulation. A quantitative method with a one-group pre-test post-test quasi-experimental design was applied to eight fifth and sixth grade students through total sampling. The results showed an increase in the average score from 33.25 to 40.38, with an average N-Gain of 0.395 (moderate). The Paired-Samples t-test showed a significance of 0.001 (< 0.05), indicating a significant difference. These findings confirm that group counseling with role playing is effective in improving students' emotional regulation.